Academics' Perceptions of Good Teaching: Assessing the Degree of Parity with Student Evaluation of Teaching Questionnaires. Issue 4 (4th July 2019) - Nabaho, Lazarus; Oonyu, Joseph; Aguti, Jessica N.
ABSTRACT: There is a dearth of studies on academics' perceptions of good teaching in transitional economies such as Uganda and the degree of parity between academics' conceptions of good teaching and the items in the student evaluation of teaching (SET) questionnaires. Against this backdrop, the article reports on a study that explored how academics at Makerere University, Uganda, perceive good teaching and compared the resultant perceptions with the items in the SET questionnaires. The study employed a qualitative approach and data was collected by using semi-structured interviews and reviewing documents. Thematic analysis was employed to analyse the data from the interviews while the data from the documents was analysed using content analysis. The findings showed that academics perceive good teaching as: being knowledgeable; being student-centred; demonstrating good communication skills; undertaking research-based teaching; demonstrating professionalism; being approachable; and being organised. Finally, the findings demonstrated a convergence between academics' perceptions of good teaching and most of the items in the SET questionnaires.